Incidence and clinical outcomes of neonatal sepsis in neonatal intensive care unit admissions: a hospital-based study - Jahan, Ishrat; Akter, Jesmine; Ferdousi, Juiyena; Sultana, Zakia; Sabrin, Zinia (International Journal of Research in Medical Sciences, 2026)
Background: Neonatal sepsis is among the leading causes of mortality and morbidity among neonates, particularly in developing countries. There is limited data regarding the clinical presentation and epidemiological pattern of neonatal sepsis in Bangladesh. This study aimed to ascertain the incidence, clinical profile, and predictors of mortality of neonatal sepsis in a tertiary care center. Methods: A retrospective observational study was conducted in Bangladesh Specialized Hospital (BSH), Dhaka, between January 2023 and December 2024. Among 576 neonatal intensive care unit (NICU) admissions, 66 neonates with sepsis diagnosed after clinical and laboratory criteria were observed. Data were extracted from electronic medical records related to demographics, clinical presentation, laboratory findings, and outcomes. Binary logistic regression analysis was performed to identify the predictors of mortality. Results: The incidence of neonatal sepsis was 11.45% (66 out of 576 NICU admissions), with a mortality rate of 6.06% (4 out of 66 cases). Male neonates predominated (60.6%), and the majority were preterm (74.2%). All affected neonates were very low birth weight infants (<1500 g), with a mean birth weight of 1000 ± 320 g. Late-onset sepsis was more common than early-onset sepsis (59.1% vs 40.9%). Respiratory distress syndrome was observed in 66.7% of cases, and 27.2% required continuous positive airway pressure support. Blood culture positivity was detected in 24.2% of cases, while elevated C-reactive protein levels were present in 71.2%. The mean duration of NICU stay was 13.4 ± 6.7 days. Independent predictors of mortality included positive blood culture (AOR=5.21, p=0.012), thrombocytopenia (AOR=4.82, p=0.022), and hypoglycemia (AOR=6.34, p=0.010). Conclusions: Neonatal sepsis accounted for 11.45% of NICU admissions and had a relatively low mortality (6.06%). Most cases occurred in preterm, very low birth weight neonates, with late-onset sepsis predominating. Positive blood culture, thrombocytopenia, and hypoglycemia were the key predictors of death, supporting early risk stratification and prompt targeted management.